Peran Kinerja Keuangan Dalam Meningkatkan Harga Saham Pada Perusahaan Go Public - Tri Purwani; Ana Kadarningsih (STEKOM PRESS, 2020)
Increasing the prosperity of owners or shareholders is one of the goals of companies that have gone public. The high prosperity will increase the market performance of companies going public. The purpose of this study is to determine the role of financial performance in improving the stock price of companies going public. The population used in this research is 65 companies in the consumer goods sector that are listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. The sampling technique used purposive sampling method, in order to obtain a sample of 60 companies that meet the sample criteria. The data analysis method used in this research is multiple linear regression analysis, descriptive analysis, normality test, coefficient of determination, and t test. Financial performance variables are measured from three ratios, namely solvency ratios, profitability ratios, and activity ratios. The results showed that the solvency ratio and profitability ratio have a significant influence on the stock price of companies going public. The activity ratio shows that the results cannot affect the stock price of companies going public